2002
DOI: 10.1016/s1010-7940(02)00405-0
|View full text |Cite
|
Sign up to set email alerts
|

A four-dimensional study of the aortic root dynamics

Abstract: Aortic root expansion follows a precise chronology during systole and becomes more cylindrical - probably to maximize ejection. These findings might stimulate a more physiologic approach to aortic valve and aortic root surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 19 publications
8
109
1
3
Order By: Relevance
“…Aortic root dynamics have been extensively studied using experimental animals [15][16][17][18][19] and MDCT in humans. [20][21][22][23][24] Dimension changes have been reported by animal studies; [17][18][19] however, results from human studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic root dynamics have been extensively studied using experimental animals [15][16][17][18][19] and MDCT in humans. [20][21][22][23][24] Dimension changes have been reported by animal studies; [17][18][19] however, results from human studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Dimension changes have been reported by animal studies; [17][18][19] however, results from human studies have been inconsistent. Although a few studies have not observed significant changes in systolic and diastolic dimensions, 20,21 a recent study reported significant changes to the aortic annulus during the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The leaflets are reinforced with collagen giving the structure physiological material characteristics [6][7][8][9][10]. The material properties of the valve model that were considered for the study are tabulated in Table 2 below …”
Section: Materials Modelmentioning
confidence: 99%
“…To understand the folding mechanism of the valve leaflets, study of the mechanical behavior of the leaflets is imperative [7]. The leaflet stresses and its deformation are given in Figure 7.…”
Section: Leaflet Analysismentioning
confidence: 99%
“…As soon as the valve starts closing and during diastole, the angle tilts back (as a shock absorber), reducing stress on the cusps. Therefore, the durability of native aortic valve seems to rely on a dynamic triad associating 1) systolic expansion of the aortic root, 2) a clover-shaped aortic orifice that embraces the bulging sinuses of Valsalva, and 3) tilting dynamics of the aortic valve (Lansac et al, 2002). Aortic valve surgery should try to preserve these baseline dynamics as much as possible using more physiologically based surgical approaches.…”
Section: The Ascending Aorta: a Dynamic Structurementioning
confidence: 99%